The Health Communications Assessment Checklist: a teaching tool for uncovering bias in the age of AI - Rebecca H. Ofrane; Taliah Canada; Amanda S. Birnbaum (Frontiers in Public Health, 2026)
Introduction The COVID-19 pandemic highlighted significant failures in United States public health communications, which were often perceived as unclear and biased, particularly among racialized and marginalized groups. As generative artificial intelligence (genAI) becomes integrated into public health practice, there is an urgent need to train the workforce to recognize and mitigate the societal biases these tools can reproduce. This study describes the development and classroom testing of a tool designed to teach these critical evaluation skills. Methods We developed the “Health Communications Assessment Checklist,” a 14-question pedagogical tool based on the CommunicateHealth Framework for Equity-Centered Health Communication and the CDC’s Guiding Principles for health equity. The checklist was tested during the 2024–2025 academic year in two graduate-level courses ( n = 55 students) at a large public university. The single-lesson exercise required students to use ChatGPT-4o to generate health communication content and then apply the checklist to critique the output for clarity, relatability, actionability, and inclusivity. Results Post-exercise surveys and classroom discussions indicated positive student engagement and self-reported skill-building in critical assessment. A key finding was that students leaned heavily on their diverse individual identities and lived experiences to identify subtle biases that the AI generated. Furthermore, the checklist acted as a self-assessment tool, helping students identify gaps in their own knowledge of communication implementation. Feedback led to iterative improvements of the tool. Conclusion The Health Communications Assessment Checklist is a simple, modifiable, and promising pedagogical tool for public health education. By centering equity and reflexivity, it helps prepare the future workforce to critically manage AI-generated content, ensuring health communications are inclusive and effective in promoting health equity.